Analysis of the learning object-oriented programming factors - Qais Ali Batiha; Nazatul Aini Abd Majid; Noraidah Sahari; Noorazean Mohd Ali (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Students often feel overwhelmed by object-oriented programming courses. They find it difficult and complex to learn, requiring a high cognitive load to use the concepts in coding. These issues lead to demotivation in learning programming. This research aims to identify and verify factors that contribute to learning object-oriented programming from two perspectives: interviews and surveys. A literature review was conducted to identify these factors, followed by interviews with five experts who have been teaching object-oriented programming for over ten years to confirm them. Based on the interview results, a questionnaire was developed and administered toÂ 31 bachelor students and 19 lecturers with masterâ€™s or doctorate degrees in computer science. The responses indicated that the identified factors were acceptable, with scores ranging from 3.74 to 4.65. The outcomes of this study are a set of factors that should be considered in a programming environment to improve the teaching and learning of object-oriented programming and make it more accessible and engaging for students.